Imaging resolution of biocatalytic activity using nanoscale scanning electrochemical microscopy - Abad, José M. (2018)
Scanning electrochemical microscopy represents a powerful tool for electro(chemical) characterization of surfaces, but its applicability has been limited in most cases at microscale spatial resolution, and the greatest challenge has been the scaling down to the nanoscale for fabrication and the use of nanometer-sized tips. Here, Pt nanoelectrodes with nanometer electroactive area were fabricated and employed for imaging a distribution of gold nanoparticles (AuNPs) and bioelectrocatalytic activity of a redox-active enzyme immobilized on gold surfaces.